(untitled) (Fiep Bulletin - online, 2013)
The studies about the female work and the woman’s insert as enterprising and entrepreneur demonstrates the professional growth of these as true " heads of the family ". This evolution in the job market brings a series of advantages for the woman, but also negative factors. The objectives and justification of this paper consist of diagnosing the work ability (work ability index WAI) , and aspects of the life quality in the cities of Viçosa and Florianópolis, in the period between 2006 and 2008. For the research it was possible to observe in the requirement capacity for the work that the researched women are classified with enough punctuation to affirm that your capacity should be maintained and even having stimulated for next years. The other objective of the research, to diagnose the quality of life related to the health through the components cardio-respiratory, flexibility and body composition, it demonstrated that the women entrepreneurs don’t still stop a great index in this aspect. The variations found in the different requirements for the health they demonstrate that an attention is not had to your health of the general point of view. And in all the components there is an intervention need the short and medium period because, otherwise, the exhibition to the risks for the health can become evident and even harming the professional acting of these.